Law No. 125 Of The Year 2010 On The Priority Of Workers Rights = قانون رقم 125 لسنة 2010 بشأن مرتبة امتياز حقوق العمال - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic.